Primary carcinoid tumor of the ovary presenting with carcinoid heart disease - Albareda, Judit (2020)
Primary ovarian carcinoid tumor is a rare neoplasm characterized by the production of vasoactive substances that enter the bloodstream and give rise to the so-called carcinoid syndrome. These substances may also cause fibrotic plaques in the heart valves, mainly those in the right cardiac chambers. We describe the case of a primary ovarian carcinoid tumor with tricuspid valve involvement in which the diagnosis was prompted by identification of cardiac involvement. Knowledge of the clinical manifestations of neuroendocrine tumors is important in diagnosis and patient management. Recognition of typical clinical features may help suggest the correct diagnosis. Multidisciplinary discussion allows the formulation of a comprehensive management strategy involving endocrinologists, cardiologists, oncologists, pathologists, anaesthesiologists, gynaecologists and heart surgeons.